Indoor environmental quality and achieving performance goals for classroom enhancement: A systematic literature review and bibliometric analysis - Dedar Salam Khoshnaw; Faris Ali Mustafa; Tamás János Katona; Bálint Baranyai (Results in Engineering, 2025)
School structures are crucial in shaping the upcoming generation's perspective on the future's sustainability. Therefore, to improve indoor environmental quality (IEQ) in school classrooms, four performance goals (PG) should be considered. These goals include reducing energy consumption, ensuring overall comfort, promoting occupant health, and enhancing student productivity. Ten holistic approach design methods (HAD) were identified to achieve these objectives. Despite the significant attention this field has garnered, there is uncertainty regarding the potential of different HAD types to influence the PG in various climate conditions. To address this uncertainty, 135 papers were reviewed across nine databases. This paper demonstrates the combined IEQ and key PG on enhancing classrooms through a systematic literature review and bibliometric analysis conducted to assess the development of this field. Then, the investigated HAD was introduced into PG in different climate zones. The review revealed that almost all HAD tested in the temperate zone (C) successfully achieved the goals. Conversely, tropical (A), dry (B), and cold (D) zones faced significant environmental challenges, complicating the implementation and effectiveness of these HAD. This review concluded that enhancing classrooms’ IEQ with HAD necessitates comprehensively considering multiple HADs rather than individual ones. Furthermore, most studies in climates A, B, and D have only focused on a few HAD aspects, resulting in substantial variations in the depth of research among different HAD categories and the applicability of PG in different climate zones. The result guides the selection of an appropriate HAD that is suitable for various climate zones to achieve PG and better IEQ in classrooms.